2020
DOI: 10.1038/s41598-020-74696-4
|View full text |Cite
|
Sign up to set email alerts
|

Land subsidence contributions to relative sea level rise at tide gauge Galveston Pier 21, Texas

Abstract: Relative sea level rise at tide gauge Galveston Pier 21, Texas, is the combination of absolute sea level rise and land subsidence. We estimate subsidence rates of 3.53 mm/a during 1909–1937, 6.08 mm/a during 1937–1983, and 3.51 mm/a since 1983. Subsidence attributed to aquifer-system compaction accompanying groundwater extraction contributed as much as 85% of the 0.7 m relative sea level rise since 1909, and an additional 1.9 m is projected by 2100, with contributions from land subsidence declining from 30 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…The overall methodology of the present research is shown in Figure 5. The relative sea-level rise is defined as the sum of the total sea-level rise due to global warming (called absolute sea-level rise) and due to land subsidence [11]. In the absence of any land subsidence, the relative sea level observed at a tide gauge station is considered equal to absolute sea level.…”
Section: Methodsmentioning
confidence: 99%
“…The overall methodology of the present research is shown in Figure 5. The relative sea-level rise is defined as the sum of the total sea-level rise due to global warming (called absolute sea-level rise) and due to land subsidence [11]. In the absence of any land subsidence, the relative sea level observed at a tide gauge station is considered equal to absolute sea level.…”
Section: Methodsmentioning
confidence: 99%
“…Regional seasonal thermal variations in sea level range up to approximately 6 in. Liu et al (2020) quantified the subsidence component of RSLC in Galveston to be approximately 30% of the total SLC in 2018. However, subsidence is a decreasing proportion of RSLC due to the increasing rate of GMSL increase, as discussed by Liu et al…”
Section: Relative Sea Level Change (Rslc)mentioning
confidence: 99%
“…Hardware, software, and firmware work together to build a sophisticated regional geodetic infrastructure for high-accuracy and high-precision GNSS monitoring. HoustonNet data and its products have been used widely by researchers from subsidence districts, the USGS, universities, and private consulting companies for subsidence (e.g., Engelkemeir et al 2010;Bawden et al 2012;Qu et al 2015;Yu and Wang 2016;Thornhill and Keester 2020), faulting (e.g., Khan et al 2014;Liu et al 2019;Qu et al 2019), coastal flooding (e.g., Shirzaei 2019, 2021), and sea-level change studies (e.g., Liu et al 2020;Zhou et al 2021). Data analysis methods have been mentioned sporadically in previous publications.…”
Section: Introductionmentioning
confidence: 99%